Electrochemical behaviour of copper in alkaline glycine solutions - O'Connor, G.; Lepkova, Katerina; Eksteen, Jacques; Oraby, Elsayed (Elsevier, 2018)
© 2018 Elsevier B.V. The fundamental electrochemical properties of the copper-glycine system were investigated in this study to understand the factors that affect the dissolution of metallic copper. Potentiodynamic polarisation measurements were carried out over the pH range 9.0 to 11.5, at temperatures of 22 °C and 60 °C and glycine concentrations 0.1 M and 0.3 M. A window for maximum corrosion current was determined to be between pH 10.0 and 10.5 with a maximum at 60 °C and 0.3 M glycine. Passivation was only observed at pH values >10.5, and then only at potentials above 0.4 V (vs SHE) for quiescent solutions. This passivation potential increased with the rotation speed of the copper electrode. The passive layer broke down after a short rest at the open circuit potential, which allowed reactivation of the surface and high initial currents to briefly flow until the layer re-formed. Potential-step and capacitance measurements are consistent with the formation of a duplex oxide layer of Cu2O and CuO that thickens with increasing potential. The copper glycinate complex itself also acts as an oxidising agent, the effectiveness is increased with its concentration and the concentration of free glycine. Free glycine is oxidised irreversibly above 1.2 V (vs SHE).